Genetic Variability and Character Association in Some Native Orchid Species (Dendrobium spp.) (The Agriculturists, 2012)
An experiment was carried out using 20 native Dendrobium orchids in Completely Randomized Design (CRD) with three replications at the Orchidarium of Landscape, Ornamental and Floriculture Division, HRC, BARI, Gazipur during the period January 2007 to June 2007 to estimate genetic variability, genetic parameters and correlation coefficient among different flower components. Highly significant variations were observed among the genotypes for all the characters. High broad sense heritability with high genetic advance was observed in spike length (94.00% and 98.29), rachis length (95.34% and 93.85), flower durability (94.00% and 89.00) and floret number (70.50% and 65.47) indicating additive gene action, suggesting the possibility of improvement of these traits through selection.  Other characters exhibited moderate broad sense heritability with low genetic advance. The number of florets per spike recorded a highly significant association with flower durability, rachis length and spike length. Durability of flower had significant positive correlation with rachis length, flower size and spike length at both genotypic and phenotypic level. Highly significant positive correlation was also found between rachis length and spike length. However, the correlation study revealed that selection of parents should be done based on characters such as floret number, rachis length and flower durability which would be useful in a breeding program. The path analysis revealed that rachis length, durability of flower and number of flowers per spike had contributed maximum direct effects on flower yield, indicating the importance of these three characters as selection criteria for native Dendrobium orchid. DOI: http://dx.doi.org/10.3329/agric.v10i1.11058 The Agriculturists 2012; 10(1): 1-9